A Comparative Study of The Yorùbá News and Aláròyé Newspapers - Adefemi Akinseloyin (Yoruba Studies Review)
The Yorùbá News, since its inception in 1924, was an admiration to many. Its informative function, which covered variety of fields relevant to the grassroots, cannot be overlooked. Despite the series of scholarly writings on The Yorùbá News, much work has not been geared towards a comparative study of the newspaper with any other be it old or contemporary. In the light of this, this essay therefore attempts a comparative study of The Yorùbá News and Aláròyé, a fast-selling contemporary Yorùbá newspaper. Four editions of The Yorùbá News and two editions of the Aláròyé newspapers are selected and content-analyzed using postmodernism theory. It is observed that The Yorùbá News distanced itself from aesthetics and total bias to the grassroots while Aláròyé newspaper foregrounded aesthetic splendor and grassroots biases in its editions. In this study, language, content, and headings/headlines are employed as measures of our comparison.